Asian mergers and acquisitions : riding the wave - Chakravarty, Vikram; Chua, Soon Ghee (Wiley corporate F & A series., 2012)
A fascinating look at the unique nature of mergers and acquisitions in AsiaThe Asian market is heating up, and both local and international firms are looking to get in on the mergers and acquisitions (M & As) that are poised to play a pivotal role in the restructuring of all manner of industries. This restructuring will increase competitiveness, but to make the most of it you need to understand why M & As in Asia are unique. With Asian Mergers and Acquisitions: Riding the Wave in hand, you have everything you need to do just that. Packed with invaluable information on how Asian M & As work, the book.